Project-Based Learning as a Pedagogical Strategy for Technical Vocabulary Development - Sumarta, Ryan Puby; Hafita, Yuniar Ayu; Budiarte, Agus; Hamdani, Zohri; Silalahi, Aliong (Newinera Publisher, 2025)
Maritime English is essential for safe and effective communication in the global shipping industry, particularly in multilingual crew environments. Despite its significance, many cadets struggle to master technical maritime vocabulary due to traditional teaching approaches that prioritize grammar and general conversation. This study investigates the effectiveness of Project-Based Learning (PBL) in enhancing cadets’ mastery of maritime English technical vocabulary at Sorong Merchant Marine Polytechnic. Using a pre-test and post-test design, 20 cadets participated in simulation-based projects involving navigation planning, safety procedures, and maritime reporting. The results revealed a significant improvement in vocabulary acquisition, with average scores rising from 50.2% in the pre-test to 78.0% in the post-test. Statistical analysis using a paired-sample t-test confirmed the significance of this increase (p < 0.05). The findings suggest that PBL not only improves technical vocabulary comprehension but also supports the development of practical communication skills, critical thinking, and teamwork key competencies in maritime professions. This study recommends the integration of PBL into Maritime English curricula to better prepare cadets for real-world operational demands.